The impact of some morphological characteristics on running 200 meters - A. Maliqi; Q. Ramabaja; L. Ramadani; B. Latifi (Kazimierz Wielki University, 2021)
The knowledge of morphological development and their impact on motor skills in short-distance athletes should be one of the main concerns of athletics coaches, because any scientific research in the field of physical culture and sports is about proving the development and evaluation of anthropological characteristics which are responsible for achieving success in athletics. This paper explores the impact of some anthropometric features on running 200 meters. The aim is to establish the link between the anthropometric and specific characteristics of running 200 meters, as a predictive system of running at 200 meters as a criterion system. The research was conducted by 60 male students aged 17±6months, in the gymnasium "Zenel Hajdini" Gjilan. The measurements were executed during September in the hall of the gymnasium, while the 200, meter runs in the stadium "City stadium "Gjilan. The only condition that was used during the determination of the sample was: that the students are involved in regular physical education classes (and on the day of the measurement be healthy, without the flu, cold or other symptoms).The variables which are applied in this research have been 8 anthropometric variables and 1 motor-specific variables. The results obtained after their processing indicate that the impact of anthropometric variables is higher in running at 200 meters. Short distance running and long-distance running reduces the impact of anthropometric parameters whereas the influence of metabolic factors of energy production is increased. These results were also confirmed using regression analysis, so that groups of predictors of anthropometric characteristics, specific motor skills that statistically significantly influenced each variable of individual criteria. The world records below the 19.20-second limit, in the 200 m, near the 19-meter limit, show not only the high level of sports, but also the strong impact on the growth, especially of strength indicators, speed-strength, explosive force, as main and applied motor skills in sports and athlete's everyday life.